Effects of Glucose and Lime Levels on the Growth and Water Quality of Chlorella ellipsoidea Cultivation - Rapeepan Yongyod; Pichasit Sangmek; Narong Kamolrat (Environment and Natural Resources Journal)
This study aimed to investigate the effects of glucose and lime concentrations in the culture medium on growth of Chlorella ellipsoideaand water quality during the cultivation. The experiment included seven treatment groups:a control group (0.5 g/L glucose, 0.4 g/L lime) and groups with reduced glucose concentrations (0.4, 0.3, 0.2, 0.1 g/L) and lime concentrations (0.2, 0.1 g/L). Cultivation lasted for 15 days, with algal growth assessed by cell counting, and water quality parameters such as alkalinity, pH, and ammonia levels analyzed daily. The results showed that the G20 (0.1 g/L glucose) group achieved highest cell densityof 7.15±0.92 × 107cells/mL on day 10, which wasnot significantly different (p>0.05) from the G40, G60, and L50 groups, but higher than the control and other treatment groups. Furthermore, alkalinity in the G20 group remained within therange of 130-187 mg/L, which is suitable for cultivation and subsequent use as feed for Moinasp. The pH values of all groups remained consistent, ranging from 7.2-8.8 throughout the experiment. Total ammonia levels remained below 1 mg/L during the first 9 days, increasingin the later period, with no significant differences between the treatment groups. In conclusion, reducing the glucose concentration to 0.1 g/L in the culture medium promoted maximum growth of C. ellipsoidea, while maintaining water quality at an optimal level. This approach offers potential for developing cost-effective algal culture media and scaling up cultivation for commercial production.